2017
DOI: 10.3390/insects8010016
|View full text |Cite
|
Sign up to set email alerts
|

Male Psyllids Differentially Learn in the Context of Copulation

Abstract: In the Asian citrus psyllid, Diaphorina citri Kuwayama, stimulatory cuticular hydrocarbons act as sex pheromone attractants. Male psyllids locate aggregations of females using those olfactory cues, as well as vibrational communication on the plant surface. Although previous research has indicated that learning plays a role in modulating female reproductive behaviors in psyllids, it is unknown whether males similarly use learning to increase the likelihood of copulatory success. We used an olfactometer-based bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 83 publications
(141 reference statements)
1
16
0
Order By: Relevance
“…Zagvazdina et al (2015) found that mean responses of D. citri males in mate-seeking bioassays decreased when barometric pressure rose or fell more than 1 standard deviation over a 24-h period. Stockton et al (2017) found that the female-odor attractiveness to male D. citri increases after successful mating. In other Hemiptera, Mazzoni et al (2017) found that male H. halys latency to initiate searching activity was lower for males that reached the female song source than those that missed.…”
Section: Discussionmentioning
confidence: 95%
“…Zagvazdina et al (2015) found that mean responses of D. citri males in mate-seeking bioassays decreased when barometric pressure rose or fell more than 1 standard deviation over a 24-h period. Stockton et al (2017) found that the female-odor attractiveness to male D. citri increases after successful mating. In other Hemiptera, Mazzoni et al (2017) found that male H. halys latency to initiate searching activity was lower for males that reached the female song source than those that missed.…”
Section: Discussionmentioning
confidence: 95%
“…Males may display increased attraction to female odors after mating experience. This appears to be a learned response and depends on a close association between female odor and mating, as males exposed to a novel odor in the context of feeding or ambient exposure failed to demonstrate attraction to the odor (Stockton et al., ). Other research on male D. citri has shown that blue females are more attractive than gray females (Wenninger & Hall, ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, there is significant need to understand the biology and ecology of this pest species. Previous research has demonstrated that learning plays a role in ecology and behavior of D. citri (Patt et al., ; Stockton et al., , ). Male and female D. citri readily associate novel olfactory and visual stimuli with specific host plant genotypes and appear to prefer the host species with which they have had previous feeding experience (Stockton et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learned mate preferences have now been displayed in multiple species (e.g. in Drosophila : Dukas, , Dukas et al ., ; in damselflies: Svensson et al ., ; Verzijden & Svensson, ; in psyllids: Stockton et al ., ). While acquiring a mate preference based on experience may allow for greater species discrimination, there are situations where individuals may actually acquire preferences for the ‘wrong’ mate, for instance, if the focal species is locally rare, or simply outnumbered by the ‘interfering’ species.…”
Section: Causes and Consequences Of Reproductive Interferencementioning
confidence: 97%